Initial configurations and business models in new technology-based firms - Hanna Rydehell; Anders Isaksson (Journal of Business Models, 2019)
Purpose:  The purpose of the paper is to analyse founders’ perceptions of initial configurations and business models in new technology-based firms (NTBFs).